Effectiveness and safety of capecitabine, irinotecan and panitumumab in advanced colorectal cancer - Yip, Pui Lam; Fung, Wai Him Brian; Lee, Francis Ann Shing; Lee, Chak Fei; Wong, Natalie Sean Man; Lee, Shing Fung (Frontiers in Oncology, 2023)
Introduction: Capecitabine, irinotecan, and panitumumab (CAPIRI-P) is a controversial regimen for metastatic colorectal cancer, with concerns regarding the efficacy and toxicity. However, its toxicity profile has been improved with dose reduction, and concerns regarding efficacy have been extrapolated from other trials. This retrospective study reports the real-world effectiveness and safety of modified CAPIRI-P (mCAPIRI-P). Material and methods: Advanced colorectal cancer patients receiving mCAPIPI-P in the first-line setting between July 2019 and December 2021 were analyzed. The progression-free survival on treatment (PFSOT) and overall survival (OS) were estimated using the Kaplan–Meier method, and the association with clinical and disease factors was analyzed using the Cox regression model. Serial changes in carcinoembryonic antigen (CEA) level and treatment toxicity were also evaluated. Results: A total of 106 patients were included, of whom 97 (92%) and 31 (29%) had left-sided primary and unresectable liver-only disease, respectively. The median PFSOT and OS were 15.4 (95% CI 12.5–18.3) and 25.5 (95% CI 17.6–33.4) months, respectively. Sixteen (51.6%) and 10 (32.3%) liver-only disease patients underwent secondary liver treatment and R0 resection, respectively. In multivariable Cox regression, CEA responders (PFSOT: HR 0.53) and CEA normalization (PFSOT: HR 0.27; OS: HR 0.28) were independent favorable prognostic factors for PFSOT and OS. Grade ≥3 toxicity rate was 43%, mainly related to uncomplicated hematological toxicities. Conclusion: The real-world data show that mCAPIRI-P is safe and effective as the first-line treatment regimen for RAS wild-type advanced colorectal cancer and warrants further study.